Assessment of Student Services of Saint Columban College: Basis for Continuous Improvement - Genesis Naparan (Philippine Association of Institutions for Research, Inc., 2019)
The main clients of every Higher Educational Institution (HEI) are the students. Their satisfaction is the utmost concern of an HEI. Thus, this paper assessed the student services of Saint Columban College using the 42 graduating students of the College of Teacher Education, Arts and Sciences (CTEAS) during the first semester of the Academic Year 2018-2019. The different student services that were assessed are the following: Admissions, Student Orientation, Guidance Program and Services, Campus Ministry, Student Assistance Program, Co-curricular Programs and Activities, Alumni, and Registrar's Services. This used a survey questionnaire adapted from the Philippine Accrediting Association of Schools, Colleges, and Universities (PAASCU) manual. This made use of weighted Mean, to sum up, the responses of the research participants. Based on the findings, Admission, Student Orientation, Campus Ministry, co-curricular activities, and Alumni got excellent ratings while Guidance Programs and services, Student Assistance program and Registrar's services got lower satisfaction from them. Therefore, the researchers suggested activities on how to serve the students better.